Depression and Health-Related Quality of Life in People with Type 2 Diabetes Mellitus: A Cross-Sectional Study - Aparna P. Patange (Journal of Coastal Life Medicine, 2023)
Background: “Type 2 diabetes mellitus (T2DM)” is a long-term metabolic condition that is accompanied by a number of physical and mental comorbidities. The purpose of the study was to evaluate the connection between depression and “Health-Related Quality Of Life (HRQoL)” in T2DM patients. Methods: On 300 T2DM patients who were attending diabetes clinics at a tertiary care hospital, a cross-sectional study was done. The Short-Form 36 (SF-36) questionnaire was used to measure HRQoL, and the Patient Health Questionnaire-9 (PHQ-9) was used to measure depression. The data were summarized using descriptive statistics, and was evaluated for the connection between depression and HRQoL. Results: Females made up 55.3% of the study participants, with a mean age of 54.2 10.8 years. While the mean SF-36 score was 53.220.6 and indicated a poor HRQoL, the mean PHQ-9 score was 10.15.6, indicating a moderate level of depression. The results demonstrated a significant relationship between depression and low HRQoL (p=-0.43, =-0.43). Additionally, the presence of comorbidities like obesity, dyslipidemia, and hypertension was linked to poor HRQoL (p0.05). Conclusion: In conclusion, depression is a frequent comorbidity in T2DM patients and significantly impairs HRQoL. To enhance the HRQoL of individuals with T2DM, diabetes clinics should therefore employ frequent depression screening and suitable therapy measures.